2013
DOI: 10.1128/mbio.00356-13
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Origin for a Human Pandemic Clone of Community-Associated Methicillin-Resistant Staphylococcus aureus

Abstract: The importance of livestock as a source of bacterial pathogens with the potential for epidemic spread in human populations is unclear. In recent years, there has been a global increase in community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections of healthy humans, but an understanding of the different evolutionary origins of CA-MRSA clones and the basis for their recent expansion is lacking. Here, using a high-resolution phylogenetic approach, we report the discovery of two emergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 36 publications
(49 reference statements)
5
180
1
2
Order By: Relevance
“…It is a leading cause of bovine mastitis worldwide [43,77,79,80] and is found occasionally in small ruminants, pigs, and humans. It was determined that the human strains originated from a bovine to human host jump believed to have occurred approximately 40 years ago and subsequently acquired methicillin resistance [81]. MSSA CC97 strains are still circulating in humans [82,83].…”
Section: Cc97mentioning
confidence: 99%
“…It is a leading cause of bovine mastitis worldwide [43,77,79,80] and is found occasionally in small ruminants, pigs, and humans. It was determined that the human strains originated from a bovine to human host jump believed to have occurred approximately 40 years ago and subsequently acquired methicillin resistance [81]. MSSA CC97 strains are still circulating in humans [82,83].…”
Section: Cc97mentioning
confidence: 99%
“…CC398 is not limited to large livestock animals alone; it has also been reported in poultry [18,122], manure from chicken farms and soil fertilized with this manure [123]. However, the numbers of MRSA ST398-t011-SCCmec V isolated from chickens are lower (0-28%) than in pigs (82-92%) on the same farm [124].…”
Section: Poultry Mrsamentioning
confidence: 91%
“…LA-MRSA S. aureus CC398 is not alone in the ability to adapt. A phylogenetic study of S. aureus CC97 strains that originated from livestock and caused human infections in Asia, Europe, and North and South America indicated that in the process of adapting to the human host, CC97 acquired either the SCCmec IV or V cassete and the φSa3 containing an immune evasion cluster [123]. A more recent study in the United States demonstrated that 22% of 30 veterinary students who were initially MRSA negative became positive after visiting MRSA-positive pig farms in Iowa but were negative again by 24 h after the visit [75].…”
Section: Frontiers In Staphylococcus Aureus 56 Frontiers In Staphylocmentioning
confidence: 99%
“…These include macrolides, streptogramins, aminoglycosides and tetracyclines, all classified as being of high importance for treating life-threatening human health conditions. [10] According to a growing body of scientific evidence a direct link can be demonstrated between antimicrobial resistance in livestock and in humans [11,12]. A recent study found that 36.6% of industrial livestock workers carried biomarkers associated with methicillinresistant Staphylococcus aureus (MRSA), compared with 19% of workers at antibiotic-free farms [13].…”
Section: Introductionmentioning
confidence: 99%